Cognitive Reading Strategies Employed by Form Three Malaysian English as Second Language (ESL) Students (LSP International Journal, 2020)
Previous studies reported that many low proficiency students have poor comprehension skills. Therefore, this research aims to study the cognitive reading strategies employed by ESL (English as Second Language) students and suggest appropriate cognitive strategies to be utilized by low proficiency students. This research was carried out in one of the secondary schools in Pasir Gudang, Johor. The purposive sample for this study consists of 60 Form 3 students (30 low proficiency and 30 high proficiency). Explanatory sequential mixed method design was used to carry out this research. The data collected via questionnaire, observation and interview for this research is analysed quantitatively and qualitatively. Descriptive analysis was used to analyse data gained from questionnaire and observation whereas for the interview data, extracts from the interviews were used to corroborate the findings. The findings reveal that the most common cognitive reading strategies employed by both group of students are skimming and translation. This research further highlights the most significant difference in reading strategies between both groups of students, which is, the high proficiency group outperformed the low proficiency group in overall strategy use, demonstrating the most frequent use of the strategies. Most prominently, in this research, the reading strategies that are deemed appropriate for the low proficiency students are highlighted. These strategies include four cognitive strategies; guessing, elaboration, summarizing and prediction.